The Use of Educational Software in Teaching Physics in the Moroccan Context - Khouna, Jalal; Ajana, Lotfi; Rhazal, Ahmed; El Mokri, Abdelilah (International Journal of Emerging Technologies in Learning (iJET), 2020)
In the educational field, many researchers have studied the role played by the educational software in teaching physics. This review study aims to analyze the use of educational software in the teaching of physics in Moroccan secondary schools between the years 2010 and 2019. The sources for the data collection process were obtained through searches on Google Scholar pages. The analysis of the results allowed us to identify the advantages and disadvantages related to the integration of educational software in teaching physics in the Moroccan context. In addition, the study contributes with a set of recommendations for future use of educational software.